2012
DOI: 10.1371/journal.pone.0030545
|View full text |Cite
|
Sign up to set email alerts
|

A Genome Wide Association Scan of Bovine Tuberculosis Susceptibility in Holstein-Friesian Dairy Cattle

Abstract: BackgroundBovine tuberculosis is a significant veterinary and financial problem in many parts of the world. Although many factors influence infection and progression of the disease, there is a host genetic component and dissection of this may enlighten on the wider biology of host response to tuberculosis. However, a binary phenotype of presence/absence of infection presents a noisy signal for genomewide association study.Methodology/Principal FindingsWe calculated a composite phenotype of genetic merit for TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
5
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 47 publications
2
70
5
7
Order By: Relevance
“…Additionally, several genome regions identified as candidates in genome wide association studies of BTB traits in British and Irish herds showed no correspondence here (Finlay et al, 2012; Bermingham et al, 2014). These disjunct results may not be surprising given that the present study is designed to detect variants segregating between zebu and European cattle breeds which are likely different to those that segregate within European herds.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, several genome regions identified as candidates in genome wide association studies of BTB traits in British and Irish herds showed no correspondence here (Finlay et al, 2012; Bermingham et al, 2014). These disjunct results may not be surprising given that the present study is designed to detect variants segregating between zebu and European cattle breeds which are likely different to those that segregate within European herds.…”
Section: Discussionmentioning
confidence: 76%
“…We identified six microsatellite markers significantly associated with at least one BTB trait (see Tables 3-5 A recent study of genome-wide association which used high density SNPs (single nucleotide polymorphisms) has identified three SNPs in a 65 kb genomic region on chromosome 22 associated with bovine tuberculosis susceptibility in Irish dairy cattle [14]. This genomic region has been found to contain gene SLC6A6 which is known to function in host immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no particular gene known to be responsible for differences in BTB infection susceptibility in cattle, natural resistant associated macrophage protein 1 (NRAMP1) was a known candidate gene; it is associated with natural resistance to infection with Mycobacterium spp., in cattle [12,13]. Recently, a genome-wide association study on Holstein-Friesian herds in Irish cattle that used the bovine 50 k SNP chip has identified three SNPs in a 65 kb genomic region on chromosome 22 associated with BTB susceptibility [14]. These studies provide substantial evidence that polymorphisms in the genome sequence play an essential role in determining resistance/ susceptibility to BTB infection.…”
Section: Introductionmentioning
confidence: 99%
“…From an economical and epidemiological point of view it would be important to select for disease resistant animals in order to decrease steadily the presence of CLA in goat herds. Although the application of genomic technologies, mainly applied in dairy cattle, can decrease the generation interval and boost genetic gain compared with traditional phenotypic selection, it is still important to perform genome wide association studies for infectious diseases to pinpoint and localise the genetic variations that have an effect on health traits, in cases where no effective therapy or prophylaxis are available, as in the case of bovine tuberculosis (Allen et al 2010;Finlay et al 2012;Bermingham et al 2014;Zare et al 2014;Richardson et al 2016) and bovine paratuberculosis (Settles et al 2009;Kirkpatrick et al 2011;Minozzi et al 2012;van Hulzen et al 2012;Alpay et al 2014;Pauciullo et al 2015), allowing the possibility to include the genetic approach as a complementary aid for disease incidence reduction. Recent developments in the animal genome sequencing technologies have allowed the application of a series of methods designed to identify regions of the genome linked or that affect certain characters of economic interest in cattle (e.g., production and/or resistance to diseases in dairy cattle) (Minozzi et al 2013) and in small ruminants, suitable when pedigree information is not available or unreliable.…”
Section: Genome Wide Association Analysismentioning
confidence: 99%